Relationships between the development of numerical abilities and phonological awareness in young age - Györkő, Enikő; Gyimes, István László (Acta Cultura et Paedagogicae, 2023)
Background: Previous neuropsychological studies pointed out that amongst the various cognitive skills leading towards the development numeracy; language skills may have an important, while mostly overlooked role. Out of the numerous language skills, phonetic awareness seems to aid the development of arithmetic skills. Aims: This research aims to explore the relationship between phonetic awareness and the development of numerical skills in young children. Methods: In this research, children aged 5-6-7-year-old (who were still in kindergarten) were included. We measured their numerical skills using Number Sense Screener and their phonemic awareness using in study. Results: Regression analysis showed a linear relationship between phonemic awareness and arithmetic skills in children at 6 and 7 years old. Conclusion: Our results indicate a link between the development of phonemic and arithmetic skills. Furthermore, there is evidence to suggest that the development of these aforementioned skills can predict success in later educational performance.